Pelatihan Assembler Edu untuk Meningkatkan Keterampilan Guru Merancang Project-based Learning Sesuai Kurikulum Merdeka Belajar - Saptono Nugrohadi; Muchamad Taufiq Anwar (Universitas PGRI Semarang, 2022)
This study aims to determine and describe: 1) student satisfaction regarding the introduction of Project Based Learning (PjBL) and Pancasila Student Profile training using Assembler Edu, 2) the relevance of PjBL introduction training and Pancasila Student Profile using Assembler Edu with the main functions of the teacher, and 3) Enter the teachers regarding the introduction of PjBL training and the Pancasila Student Profile using Assembler Edu. This research is a descriptive quantitative research. The analytical technique used is descriptive analysis using Python tools. In this study, training was held so that teachers could create projects using the Assembler Studio. The results of data analysis showed that the feedback or responses that the teachers showed related to the training carried out by the teachers were very good. the teachers are satisfied with the Assembler Edu training held by the teacher. The training that is followed can provide benefits for teachers in understanding the main tasks of teachers as students of Pancasila. In addition, the relevance of the training provided to teachers, and motivating teachers to be able to provide learning with PjBL according to the independent learning curriculum that utilizes Assembler Edu.